IMPLEMENTASI PEMBELAJARAN IPS TERHADAP PEMBENTUKAN KARAKTER SISWA KELAS 4 DI UPT SDN 75 BENTANG - fadhila amalia pertiwi; Andi Zulqaedah Jafar; Fitri Yanty Muchtar (STKIP Subang, 2026)
Social Studies (IPS) is a subject that plays a crucial role in shaping good citizens. Therefore, learning Social Studies is crucial at the elementary school level, as it lays the foundation for understanding and understanding how to live socially in society. This study aims to determine the implementation of IPS learning in character formation for students in elementary schools. This research was conducted in Takalar Regency, at the UPT SD Negeri 75 Bentang on September 29, 2025, using a qualitative descriptive research method. The data sources were primary and secondary data, with data collection techniques including observation, interviews, and documentation. The subjects were teachers and students at the elementary school. The results of this study reveal that character is an individual trait, personality, disposition, and behavior that a person possesses throughout life. Character is a key aspect in shaping a person's qualities, enabling them to become a noble person. Social studies education plays a crucial role in producing quality students, namely individuals capable of critical, creative, logical thinking, and initiative in addressing emerging social phenomena and problems in society.